THE STUDY OF COVID-19 PANDEMIC'S IMPACT ON CONSTRUCTION SUPERVISION FROM SUPERVISORY CONSULTANT'S PERSPECTIVE - Budiawan, Ramon
COVID-19 is an airborne disease and has been declared as a pandemic because it spreads so fast around the world. As a result, many industries were affected, one of which was construction. Many projects experienced delays and increased project costs. In addition, the supervision process carried out by the supervisory consultant was also affected. Various efforts have been made by the government by issuing regulations and policies so that the implementation of construction services can run during the COVID-19 pandemic. This has resulted in the supervisory consultant having to adapt so that activities and tasks can be carried out. Therefore, this study intends to obtain an overview of the impact of the COVID-19 pandemic on supervisory activities and identify important factors in adapting new construction supervision habits from the perspective of supervisory consultants. Data collection was carried out by distributing questionnaires and interviews to supervisory consultant personnel based on experience before and during the COVID-19 pandemic. By using a qualitative descriptive analysis, it was found that the majority of supervisory consultants adapted the application of communication technology and personnel arrangements in the field during the COVID-19 pandemic. It is scarce to find construction supervisors who add to the supervision contract addendum. There are differences in the implementation of construction supervision tasks between before and during the pandemic, there were 17 tasks that were not carried out properly due to the COVID-19 pandemic. There are 5 tasks that are well executed. A total of 4 additional tasks are proposed in the project's OHS monitoring activities. The elements that need to be paid attention to by the supervising consultant include pre construction meeting, requests to start work, joint surveys and joint inspections, supervision of work in progress, supervision of technical specifications, assistance and supervision of contractor Action Plans, regular meetings, and implementation COVID-19 health protocol. In conclusion, the adaptation of supervisory consultants has an effect on project performance, especially on project OHS performance. The proposal for the development of supervision in the future is to add a clause of special conditions such as a pandemic to the construction contract. In addition, the use of surveillance technology such as drones or CCTV should be included in the supervision contract to make it easier for project owners to know the progress of project implementation. If the project is delayed and the supervision contract has expired, it is expected that the supervision contract is extended by the project owner with the aim of supervising the critical condition of the project. To support the activities and supervisory duties, there is good coordination and cooperation between the all parties involved in the project. Compliance with health protocols related to COVID-19 also plays an important role in project implementation.